Data of clavulanic acid and clavulanate-imidazole stability at low temperatures (2019)
Clavulanic acid (CA) is a b-lactam antibiotic with a strong inhibitory effect on b-lactamase enzymes. CA is produced in submerged cultures by the filamentous Gram-positive bacterium Streptomyces clavuligerus (S. clavuligerus). CA is an unstable molecule in aqueous solution and its stability depends strongly on temperature and concentration. In this contribution, the experimental data of CA stability, produced in chemically defined media and exposed to temperatures between 80 and 25 C, are presented. The chromophore clavulanate-imidazole (CAI) is commonly used for analysis and quantification of CA samples by High Performance Liquid Chromatography (HPLC); nevertheless, this molecule is also susceptible to suffer degradation in aqueous solution, potentially affecting the quantification of CA. Data of CAI concentration for samples conserved at 4 C and 25 C are also presented. A reversible-irreversible kinetic model was applied to estimate the degradation rate of CA. Data from numerical simulations of CA degradation using the proposed kinetic model are also graphically presented. The data show the clavulanic acid instability in fermentation broths, in a range of temperatures of interest for bioprocess operation, downstream processing, samples quantification, conservation and storage.